Effects of safinamide on the glutamatergic striatal network in experimental Parkinson's disease. (15th June 2020) - Sciaccaluga, Miriam; Mazzocchetti, Petra; Bastioli, Guendalina; Ghiglieri, Veronica; Cardinale, Antonella; Mosci, Paolo; Caccia, Carla; Keywood, Charlotte; Melloni, Elsa; Padoani, Gloria; Vailati, Silvia; Picconi, Barbara; et al.
Abstract: Objective: The aim of the study was to evaluate electrophysiological effects of safinamide on the intrinsic and synaptic properties of striatal spiny projection neurons (SPNs) and to characterize the possible therapeutic antiparkinsonian effect of this drug in dopamine (DA) denervated rats before and during levodopa (l -DOPA) treatment. Background: Current therapeutic options in Parkinson's disease (PD) are primarily DA replacement strategies that usually cause progressive motor fluctuations and l -DOPA-induced dyskinesia (LIDs) as a consequence of SPNs glutamate-induced hyperactivity. As a reversible and use-dependent inhibitor of voltage-gated sodium channels, safinamide reduces the release of glutamate and possibly optimize the effect of l -DOPA therapy in PD. Methods: Electrophysiological effects of safinamide (1–100 μM) were investigated by patch-clamp recordings in striatal slices of naïve, 6-hydroxydopamine (6-OHDA)-lesioned DA-denervated rats and DA-denervated animals chronically treated with l -DOPA. LIDs were assessed in vivo with and without chronic safinamide treatment and measured by scoring the l -DOPA-induced abnormal involuntary movements (AIMs). Motor deficit was evaluated with the stepping test. Results: Safinamide reduced the SPNs firing rate and glutamatergic synaptic transmission in all groups, showing a dose-dependent effect with half maximal inhibitory concentration (IC50 ) values in the therapeutic range (3–5 μM). Chronic co-administration of safinamide plus l -DOPA in DA-denervated animals favored the recovery of corticostriatal long-term synaptic potentiation (LTP) and depotentiation of excitatory synaptic transmission also reducing motor deficits before the onset of LIDs. Conclusions: Safinamide, at a clinically relevant dose, optimizes the effect of l -DOPA therapy in experimental PD reducing SPNs excitability and modulating synaptic transmission. Co-administration of safinamide and l -DOPA ameliorates motor deficits. Highlights: Safinamide reduces striatal synaptic transmission in experimental parkinsonism. Safinamide reduces the firing rate of striatal neurons in emi-parkinsonian rats. Safinamide delays the onset of l -DOPA-induced dyskinesia in Parkinson's disease model.